PERAN MANAJEMEN PEMBIAYAAN BANK SYARIAH DALAM MENDORONG PEMBANGUNAN BERKELANJUTAN - Anggi Anggeriani Br Ketaren; Vania Khairunisa lubis; Muhammad Ikhsan Harahap (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze how Islamic bank financing management contributes to sustainable development through the integration of sharia principles, environmental responsibility, and social welfare. Using a qualitative descriptive method based on literature synthesis, regulatory documents, and secondary data on sustainable financing and national emission trends, this study examines the implementation of financing practices at Bank Syariah Indonesia (BSI) and the role of green financing in achieving the Sustainable Development Goals (SDGs). The results indicate that Islamic financing management significantly supports SDGs through inclusive financing, green financing allocations, environmental impact assessments, and digital transformation that enhances efficiency and reduces carbon footprints. The findings also show that BSI’s sustainable financing reached Rp 41.91 trillion in 2022, while national CO₂ intensity remained in the range of 47–57 Mt, highlighting the urgency for Islamic banks to strengthen their contribution to climate mitigation. Overall, Islamic financing management plays a strategic role in promoting economic growth, social equity, and environmental sustainability in alignment with maqasidal shariah.